Teacher and Student Perception through Online Literature Circle on Reading Comprehension: a Phenomenology Study - Musdalifah Musdalifah (Universitas Muhammadiyah Jember, 2021)
Online learning has been applied during the COVID 19 pandemic. This is one of the challenges in a teaching-learning activity that changes into a new process from face-to-face learning to online learning. It must be done by the teacher to deliver some materials to their students. One of the activities in teaching English language is reading comprehension. In this case, reading activity is useful for students related to this pandemic situation. Implementing online teaching by using online literature circles for the students at vocational high school is suitable to make them more creative and independent in the learning process. Teaching reading as an activity in learning English in vocational high school still uses an intensive method, it makes students are required to understand the reading text by being able to answer questions such as multiple choice or essays. Online literature circle activity that engages students to share their idea and discuss through a reading activity. The purpose of this study was to explore the experiences of students and the teacher perception of online literature circles through reading comprehension. The material that was applied in the research is about the application letter. The study involved 15 students at class twelve of network computer techniques at vocational high school in Ibrahimy 2 Sukorejo, Situbondo. Qualitative design is used in this study especially phenomenological research framework, with a deep interview by WhatsApp. The data was documented by using a message on WhatsApp.